A new cost-performance grid to compare different flood modelling approaches. Issue 3 (17th February 2021) - Hdeib, Rouya; Moussa, Roger; Colin, François; Abdallah, Chadi
ABSTRACT: The wise selection of modeling approaches with an appropriate level of complexity for the study objectives is critical for robust inference. In this paper, the structure of a cost–performance grid designed for flood modeling is presented. The grid is developed to compare different flood modeling approaches of variable complexity and to provide guidance on the proper selection of the data-model couple. The methodology involves defining metrics to quantify the three variables: data costs, model costs, and performance. Preliminarily, 18 flood modeling applications in the literature were arbitrarily selected and analyzed to guide the implementation of the grid. The cost–performance diagram allows us to trace a cost–performance curve and group applications in four zones corresponding to four modeling approaches (empirical and geomorphic, hydrological, hydraulic, and coupling). The grid is a tool to support the comparison, classification, and future selection of cost-effective modeling approaches. It is flexible and can be extrapolated to other modeling objectives.